Aspek Tattwa, Susila dan Upacara Dalam Tradisi Ngerasakin di Desa Banyuatis - Gede Mahardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Hinduism is very rich in traditions and religious ceremonies using various symbols in the implementation of their religion, the feeling tradition is one of the traditions carried out in Banyuatis Village. The feeling tradition is a form of ceremony carried out by the people of Banyuatis Village who own agricultural land and plantations as a feeling of gratitude and devotion to Sang Hyang Widhi Wasa for gifts and crops. This study aims to explore the aspects of tattwa, morals and ceremonies in the feeling tradition in Banyuatis Village. This study uses a theological approach, the type of research data is qualitative data with three data collection methods, namely observation, interviews and documentation studies. The tattwa aspect in this study can be seen from the tattwa brahma, namely the worship of Jero Sedahan. Jero Sedahan is a manifestation of God Almighty or Ida Sang Hyang Widhi Wasa as the guardian of plantations and agriculture. Aspects of morality can be seen from the form of devotion to Ida Sang Hyang Widhi Wasa which is to maintain a harmonious life between the rulers of the World. The ceremonial aspect can be seen from the offerings used in the feeling ceremony as a symbol of devotion to God Almighty or Ida Sang Hyang Widhi Wasa.